Mediation as a tool for addressing gaps in civil legislation amid economic transformation - Завальнюк, Сергій Володимирович; Завальнюк, С. В.; Zavalniuk, Serhii V.; Завальнюк, Володимир Васильович; Завальнюк, В. В.; Zavalniuk, Volodymyr V.; Завальнюк, Ірина Володимирівна; Завальнюк, І. В.; Zavalniuk, Iryna V. (Riga : Baltija Publishing, 2025)
In the contemporary context, the provision of legal support for innovative processes affecting the economic, political and social development of society is becoming increasingly significant. The economy requires legal backing to ensure stability, to minimise conflict-generating factors, and to enable effective mechanisms for achieving consensus with partners. This article explores the legal foundations, mechanisms, and practical approaches to applying the institution of mediation in resolving economic disputes in Ukraine. Furthermore, the study explores the potential of blockchain technology to address the existing gaps in civil law. Methodology. The study employs a combination of contemporary general scientific and specialised legal research methods, providing a systematic, holistic, and interdisciplinary approach to analysing the phenomenon of mediation as a mechanism for addressing legal gaps in civil law during the resolution of economic disputes. The present study employs the dialectical method to identify patterns in the evolution of legal regulation for alternative dispute resolution in Ukraine, within the framework of market relations and the rule of law. System analysis enables the consideration of mediation as an element of the legal mechanism regulating economic relations, in interaction with judicial practice, law-making, and civil law principles. The formal legal method is employed to analyse legislative acts, with a particular focus on the Law of Ukraine "On Mediation" and the Civil and Commercial Procedural Codes, with the aim of examining the application of mediation to economic disputes. Furthermore, the judicial decisions of the Supreme Court are examined. The legal modelling method is employed to formulate proposals for enhancing the regulatory framework for implementing mediation agreements in Ukraine, as well as for developing conceptual approaches to recognising such agreements as a means of bridging legal gaps in civil law. The objective of this scientific article is threefold: firstly, to examine the potential of mediation as a tool for addressing gaps in civil law during the resolution of economic disputes; secondly, to analyse current legislation and judicial practice; and thirdly, to formulate proposals for improving national law enforcement practices. The findings of the research demonstrate that mediation holds significant potential as a means of overcoming gaps in civil law, particularly in areas where proper legal regulation of economic relations is lacking, or where the existing legislation is overly formalised. Conclusion. Since 2021, Ukraine's national legislation has created proper legal preconditions for the development of mediation in economic disputes, particularly through the adoption of the Law of Ukraine "On Mediation" and corresponding amendments to procedural codes. Judicial practice demonstrates the efficacy of mediation, particularly in cases involving the suspension of proceedings for the purpose of conducting negotiations, thus signifying a gradual integration of alternative dispute resolution into the national legal system. The primary factors impeding the advancement of mediation in Ukraine are as follows: inadequate awareness among participants in economic legal relations; the absence of consistent judicial practice; insufficient institutional support and certification of mediators; and the lack of a regulated mechanism for the enforcement of mediation agreements. In order to ensure the effective implementation of mediation as a means of addressing legal gaps in the economic sector, it is necessary to: ensure proper professional training for mediators; formalise the procedure for recognition and enforcement of mediation agreements; create conditions for promoting mediation among entrepreneurs, lawyers, and judges; and adapt court-assisted mediation tools to the specifics of economic disputes.
Zavalniuk S. Mediation as a tool for addressing gaps in civil legislation amid economic transformation / S. Zavalniuk, V. Zavalniuk, I. Zavalniuk // Baltic Journal of Economic Studies. – Riga : Baltija Publishing, 2025. - Vol. 11(4). - Р. 119-125. URL: https://doi.org/10.30525/2256-0742/2025-11-4-119-125
Keywords: economy; economic transformation; alternative dispute resolution of economic conflicts; mediation; mediation agreement; civil legislation; gaps in civil legislation; legal system of Ukraine